Uji Efektivitas Ekstrak Daun Kelor (Moringa oleifera) dalam Menurunkan Kadar Asam Urat pada Mencit (Mus Musculus) Yang Diinduksi Hati Ayam - Resti Novita Sidauruk; Erida Novriani; Razoki Razoki (Journal of Pharmaceutical and Sciences, 2026)
Background: Hyperuricemia is a metabolic disorder with an increasing prevalence and a risk of developing into gout if not properly treated. The use of allopurinol as a conventional therapy is effective in lowering uric acid levels; however, it may cause side effects, thus safer natural-based therapeutic alternatives are needed. Moringa leaves (Moringa oleifera) are known to contain bioactive compounds with potential antihyperuricemic activity. Objective: This study aimed to evaluate the effectiveness of Moringa leaf extract in reducing uric acid levels in mice (Mus Musculus) with hyperuricemia induced by chicken liver. Methods: This laboratory experimental study with a controlled group design used 30 mice divided into six groups (n = 5): normal control, negative control (5% Na-CMC), positive control (allopurinol 10 mg/kgBW), and three treatment groups receiving Moringa leaf extract at doses of 70, 140, and 280 mg/kgBW. Hyperuricemia was induced using chicken liver. Uric acid levels were measured daily for 7 days using a Multicheck Nesco® device. Data were analyzed using One-Way ANOVA followed by the Tukey Post Hoc test with a significance level of p < 0.05. Results: Chicken liver induction successfully increased uric acid levels in mice in all treatment groups (baseline levels of 3.26–3.42 mg/dL increased to 8.20–8.30 mg/dL). Moringa leaf extract showed a gradual and dose-dependent reduction in uric acid levels. The dose of 280 mg/kgBW provided the most optimal reduction effect (from 8.22 mg/dL to 3.44 mg/dL on day 7; p < 0.05), approaching the effectiveness of the positive control allopurinol (from 8.30 mg/dL to 3.52 mg/dL). Phytochemical screening confirmed the presence of active compounds such as flavonoids, alkaloids, saponins, phenols, and triterpenoids which play a role in inhibiting the xanthine oxidase enzyme. Conclusion: Moringa leaf extract effectively reduces uric acid levels in mice induced with hyperuricemia, with the dose of 280 mg/kgBW being the most optimal. Moringa leaf extract has potential to be developed as a natural-based antihyperuricemic therapeutic alternative.